Bethesda Category III thyroid nodules: descriptive cytological aspects of a series - Júlia Thalita Queiroz Rocha; Rafael Guimarães Kanda; Mariangela Esther Alencar Marques; José Vicente Tagliarini; Glaucia Maria Ferreira da Silva Mazeto; Cristiano Claudino Oliveira (BMC, 2023)
Abstract Background The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) is used for cytopathological diagnosis of fine needle aspiration (FNA) of thyroid nodules (TN). Diagnosis of Bethesda Category III (CIII) has estimated malignancy rates of around 10%-30%, which vary between different institutions. Objective. To review cases of FNA interpreted as CIII thyroid nodules. To evaluate cytopathological criteria used to interpret FNA for CIII thyroid nodules and the associations between cytological and radiological aspects. To determine the malignancy rate of thyroid nodules classified as CIII, based on the correlation with surgical procedure. Methods. Retrospective study of FNA's cytologic criteria of TN classified as CIII, carried out between 2010 and 2016. The patients included in the study were those who underwent the first FNA in the service and who were diagnosed with CIII. The patients had their cytological slides and medical records reviewed to detect the conduct flow followed after the CIII diagnosis. All cases that had histological slides available of their thyroidectomy products, total or partial, reviewed. The associations between clinical, histological and cytological findings were statistically studied. Results. Among 63 patients with resected nodules, 17 (27%) were malignant, 13 of which were papillary thyroid carcinomas. Among the benign cases, 18 patients (28.1%) had chronic lymphocytic thyroiditis/Hashimoto's thyroiditis. Papillae (p = .004) was the criterion best associated with the diagnosis of malignancy. Conclusion. The malignancy rate was consistent with the rate of malignancy predicted in the TBSRTC. It is important to point out that the sample of this study is relatively small, which compromises specific evaluations and reduces the robustness of the observed data. CIII is extensively studied in the literature, however there is still a need for more precise studies regarding the correlations between cytological findings and other parameters. Probably, more than other categories, CIII may require a combination of cytological, radiological and clinical interpretation, with pathology leading role in this diagnosis process.